Titanium aluminium carbide (Ti₃AlC₂) and lanthanum hexaboride (LaB₆) as saturable absorber for pulse generation in 1.5 micron region / Suziana Omar - Omar, Suziana (2023)
Fiber laser applications are attracted to optical fibre because of its inexpensive cost, small size, and immunity to electromagnetic interference. The saturable absorber (SA) in the fibre laser cavity is essential for the passive initiation of pulses. As a result, the researchers have always been interested in SAs that can create pulse lasers with great performance and strong optical stability. The present saturable absorber has a small working bandwidth, a low damage threshold, and weak nonlinear optical properties. In this thesis, we have drawn attention to the two new materials used as SA, which are Titanium aluminium carbide (Ti3AlC2) and Lanthanum hexaboride (LaB6). Titanium aluminium carbide (Ti3AlC2) is one of the materials which belong to the MAX phase compound. It has received great attention due to its resistance to high temperature. Next, lanthanum hexaboride (LaB6) nanoparticles, an inorganic chemical of rare earths and refractory ceramic materials, it has attracted a lot of interest. The main goal of this research is to explore the potential of Ti3AlC2 and LaB6 materials in pulse generation within the 1.5-micron region. In this work, two types of saturable absorbers (SAs) were prepared based on both materials using two approaches: thin film and deposited onto D-shape fibre. These SAs were also characterized in terms of physical property, linear, and nonlinear absorptions The SA devices with linear absorption (1.9 dB -7 dB) demonstrated the wide linear absorption, enabling the SA to produce pulses over a broad range of wavelengths. The modulation depth (0.6 % - 4.2 %) demonstrated the high saturable absorption, robust pulse shaping, and stable pulsed laser operation of the SA. To generate Q-switching pulsed laser, a small cut of SA thin film was sandwiched into two fibre ferrules and inserted into laser cavity. The mode-locked pulses were generated by adding a 100 m single mode fibre (SMF) inside the laser cavity to balance the total cavity dispersion which consequently promotes the mode locking action. The SAs produced based on D-shaped fiber and thin film structure were successfully used to generate Q-switched and mode-locked lasers in the erbium-doped fiber laser cavity, demonstrating the suitability of such SA devices in the all fiber-based cavity. This is the first demonstration of using LaB6 material as a SA to generate pulses in the 1.5 μm range. The MAX phase Ti3AlC2 thin film generated a soliton mode-locked laser with a pulse width that was 5.02 ps shorter than that of other materials. Higher pulse energy for a Q-switching laser in a Ti3AlC2 thin film was 138.76 nJ. The development of a SA with strong nonlinear absorption, a high optical damage threshold, wavelength independence from bandgap, and a broad operational bandwidth was demonstrated by Ti3AlC2. These results indicate that sources for a variety of steady and reasonably priced pulsed laser generations, Ti3AlC2 and LaB6, are equally promising. Short-pulsed lasers in the 1.55-m regime are essential for applications such optical fiber networking, remote sensing, material processing, and lasers.